Influence of Porang (Amorphophalus muelleri) Cultivation On The Composition of Soil Arthropods In Tropical Agroforestry Areas In East Java, Indonesia - Leksono, Amin setyo; Yanuwiadi, Bagyo; Zaenal, Kusuma; Farid, Akbar; Maulana, Fujianor (Journal of Tropical Life Science, 2011)
This research was conducted on July to October 2010 to evaluate the effect of porang cultivation on the abundance, diversity and composition of soil Arthropods. Change in the abundance, diversity and composition of soil Arthropods was observed using pitfall traps in two study sites (Jember and Madiun). In each study site, samplings were performed in porang cultivation land and non-porang area. A total of 15 traps were put in three lines at each location. The differences in the abundance and diversity were analyzed by using multivariate analyze tests. The soil Arthropod compositions in all locations were compared with Bray-Curtis similarity index. The effect of environmental factors on the arthropod compositions was analyzed using multiple regression. The result showed that the effect of porang-cultivation was not consistent in two study sites. In Madiun, the abundance of soil Arthropods in porang cultivation land was slightly higher than that in non-porang, while the diversity was significantly higer in the former location. In contrast the those in Jember was found in vice versa situation. This study indicate that the effect of porang-cultivation was not subtantial to the composition of soil Arthropods. Therefore practice non harmful porang cultivation should be promoted as a part of agroforestry sistem in both study sites.Keywords: Agroforestry, conservation, pitfall traps Soil Arthropods composition